Using soluble urokinase plasminogen activator receptor to stratify patients for medication review in the emergency department. Issue 4 (2nd August 2021) - Bengaard, Anne Kathrine; Iversen, Esben; Kallemose, Thomas; Juul‐Larsen, Helle Gybel; Rasmussen, Line Jee Hartmann; Dalhoff, Kim Peder; Andersen, Ove; Eugen‐Olsen, Jesper; Houlind, Morten Baltzer
Abstract : Aims: To investigate whether the association between levels of medication use (including polypharmacy and potentially inappropriate medications [PIMs]) and health outcomes such as readmission and mortality is dependent on baseline soluble urokinase plasminogen activator receptor (suPAR). Methods: This registry‐based cohort study included medical patients admitted to the emergency department at Copenhagen University Hospital Hvidovre, Denmark. Patients were grouped according to their admission suPAR levels: low (0–3 ng/mL), intermediate (3–6 ng/mL), or high (>6 ng/mL). Hyper‐polypharmacy was defined as ≥10 prescribed medications. PIMs were identified based on the EU(7)‐PIM list, and data on admissions and mortality were obtained from national registries. Risk of 90‐day readmission and mortality was assessed by Cox regression analysis adjusted for sex, age and Charlson comorbidity index. Results were reported as hazard ratios within 90 days of index discharge. Results: In total, 26 291 patients (median age 57.3 y; 52.7% female) were included. Risk of 90‐day readmission and mortality increased significantly for patients with higher suPAR or higher number of medications. Among patients with low suPAR, patients with ≥10 prescribed medications had a hazard ratio of 2.41 (95% confidence interval = 2.09–2.78) for 90‐day readmission and 8.46 (95% confidence interval = 2.53–28.28) for 90‐day mortality compared to patients with 0 medications. Patients with high suPAR generally had high risk of readmission and mortality, and the impact of medication use was less pronounced in this group. Similar, but weaker, association patterns were observed between suPAR and PIMs. Conclusion: The association between levels of medication use and health outcomes is dependent on baseline suPAR.